Direct Benefit Transfer (DBT) of Fertilizer Subsidy in India–Issues and Related Aspects - Roy, Tuhin Narayan (International Journal of Bio-resource and Stress Management, 2019)
This study attempts to review, examine and analysis of present status of direct benefit transfer (DBT) of fertilizer subsidy in India from limited secondary sources of information. Fertilizer is one of the most important input for agriculture. Subsidy on fertilizer will directly deposited into the bank account of the buyers after purchasing from point of sale (PoS) auhenticated by Jandhan-Aadhar-Mobile (JAM). It has many social and economic impacts. Earlier, fertilizer subsidy involves leakages and diversions. DBT on fertilizers came into force in 2016 on pilot basis to some States. It was expected that DBT could reduce pilferage of Government’s expenditure on social aspect and help saving (1st year saving by ` 30000 cr.). The NITI Aayog (2018) showed majority of retailers and farmers are satisfied with DBT. However, some key issues such as connectivity and dealer’s margins have important roles. The conviction of the implementing authorities, stakeholder’s awareness and Infra-structural facilities are very much necessary for effective application of the scheme. Little information have been reported about the progress of DBT for economic analysis since DBT of fertilizer subsidy has been implementing throughout the country only from 2018. Many authors expect its positive impact but others express little bit concern and suggested few measures before implementation. The scheme has the sense for social welfare and, thus, concrete economic analysis will be possible on DBT on fertilizer subsidy when adequate data will be available.